Pricing double barrier options on homogeneous diffusions: a Neumann series of Bessel functions representation - Kravchenko, I.; Kravchenko, V. V.; Torba, S. M.; Dias, J. C. (International Journal of Theoretical and Applied Finance, 2019)
This paper develops a novel analytically tractable Neumann series of Bessel functions representation for pricing (and hedging) European-style double barrier knock-out options, which can be applied to the whole class of one-dimensional time-homogeneous diffusions, even for the cases where the corresponding transition density is not known. The proposed numerical method is shown to be efficient and simple to implement. To illustrate the flexibility and computational power of the algorithm, we develop an extended jump to default model that is able to capture several empirical regularities commonly observed in the literature.